Pelestarian budaya kampung polowijen: Melawan dominasi dan hegemoni budaya modern - shofa, abdullaah (Maliki Interdisciplinary Journal, 2025)
The currents of modernization and globalization pose serious challenges to the sustainability of local cultures. This article examines the symbolic resistance against the hegemony of modern culture undertaken by Kampung Budaya Polowijen in Malang City. Using a descriptive qualitative approach, the study explores cultural preservation strategies such as the revitalization of the Tari Topeng Malangan (Malangan Mask Dance), the Wilujengan spiritual procession, and cultural education programs focused on regenerating local values. Kampung Budaya Polowijen not only preserves tradition but also fosters identity and cultural resilience amidst global homogenization. This initiative reflects the practice of counter-hegemony as proposed by Gramsci and represents a form of cultural decolonization, as emphasized by Asmawati & Subekti. Digital media is also strategically utilized as a tool for cultural promotion and education. Thus, Kampung Budaya Polowijen stands as a living example of a local community that is both active and adaptive in defending cultural existence in the modern era.